Journey of the software professional a sociology of software development - Hohmann, Luke (Prentice Hall, 1997)
Crammed with advice for both developers and managers, Journey of the Software Professional covers an extraordinary range of topics - and presents them through a coherent Structure-Process-Outcome framework that helps you make sense of your own experience. You'll discover tools and techniques for building and implementing you own career development plan. You'll learn the concepts underlying well-designed system architectures and how to apply these concepts to create an architecture appropriate for your project. At the same time, you'll learn how to create organizational structures that support this architecture and manage the growth of the team over the life of the project. You'll learn how to develop long-term strategies for improving your organization's software development. And a whole lot more.
Keywords: Computer software -- Development; Soziologie; Softwareentwicklung